Wavelength and fluence dependences of the IR multiple photon dissociation of CH3NH2 to form ground state NH2 radicals - Hancock, G; Hennessy, R; Villis, T (1979)
Ground state NH2 radicals have been detected by laser excited fluorescence following the collisionless multiple photon dissociation of CH3NH2 by a pulsed CO2 laser. The variation of dissociation yield with IR laser fluence and wavelength are reported for several CO2 lines overlapping the CH3NH2ν8 band. Dissociation is more efficient at wavelengths corresponding to initial absorption in the P branch of this transition than for excitation in the Q or R branches, with the difference in efficiencies being more pronounced at lower fluences. The mechanism of NH2 production appears to be direct C-N bond fission. © 1979.